2002
DOI: 10.1038/sj.bjc.6600537
|View full text |Cite
|
Sign up to set email alerts
|

The association of breast mitogens with mammographic densities

Abstract: Radiologically dense breast tissue (mammographic density) is strongly associated with risk of breast cancer, but the biological basis for this association is unknown. In this study we have examined the association of circulating levels of hormones and growth factors with mammographic density. A total of 382 subjects, 193 premenopausal and 189 postmenopausal, without previous breast cancer or current hormone use, were selected in each of five categories of breast density from mammography units. Risk factor info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
296
16

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(348 citation statements)
references
References 51 publications
36
296
16
Order By: Relevance
“…Physical activity may influence mammographic density by favorably changing certain hormones that may be associated with mammographic density, such as sex steroid hormones. Many published studies have shown an effect of exogenous estrogens on increasing mammographic density (19), however, the only published study that examined the association between mammographic density and endogenous estrogens observed no association between total estradiol and percent density in both pre-and postmenopausal women, and an inverse association between free estradiol and percent dense tissue in postmenopausal women (20). The hypothesized mechanism of physical activity influencing mammographic density via sex hormone changes applies especially to obese postmenopausal women, who have higher levels of sex hormone concentrations than leaner postmenopausal women, due to the formation of estrogens in fatty tissue (10,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity may influence mammographic density by favorably changing certain hormones that may be associated with mammographic density, such as sex steroid hormones. Many published studies have shown an effect of exogenous estrogens on increasing mammographic density (19), however, the only published study that examined the association between mammographic density and endogenous estrogens observed no association between total estradiol and percent density in both pre-and postmenopausal women, and an inverse association between free estradiol and percent dense tissue in postmenopausal women (20). The hypothesized mechanism of physical activity influencing mammographic density via sex hormone changes applies especially to obese postmenopausal women, who have higher levels of sex hormone concentrations than leaner postmenopausal women, due to the formation of estrogens in fatty tissue (10,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined the GH-IGF signaling pathway in association with mammographic density, for both premenopausal and postmenopausal women, but the results are indifferent [43,44,34]. For postmenopausal women, however, the growth factor levels, estrogen levels and mammographic densities are lower than that for premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…For postmenopausal women, however, the growth factor levels, estrogen levels and mammographic densities are lower than that for premenopausal women. This may explain in part, why no associations between these growth factors and mammographic density have been observed for postmenopausal women [34,35,43]. Thus, the higher levels of cyclic estrogen and serum level of growth factors may be more likely to capture the aetiologically relevant exposure period, and may explain in part why the associations are more pronounced among premenopausal women [45].…”
Section: Discussionmentioning
confidence: 99%
“…48 The second mechanism involves biological interaction among epithelial and stromal cells, collagen and the breast microenvironment. 32,33 It has been shown that mitogenic followed by mutagenic activity are at least in part, responsible for high breast density and breast cancer, where individuals with both high breast density and breast cancer demonstrate similar mitogen 47 and mutagen characteristics. 48 It is well known that mitogens induce cell proliferation, primarily affecting epithelial and stromal cells leading to increased fibroglandular tissue and higher levels of breast density mostly in premenopausal women.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%
“…43,46 Mechanisms linking breast density to breast cancer Two theories have been postulated to explain the mechanisms linking breast density and breast cancer. The first mechanism involves mitogen (a chemical substance that encourages a cell to commence cell division, triggering mitosis), 47 and mutagen effects (a physical or chemical agent that changes the genetic material of an organism and thus increases the frequency of mutations above the natural background level). 48 The second mechanism involves biological interaction among epithelial and stromal cells, collagen and the breast microenvironment.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%